The Realization of Appraisal in Eulogies Given by People of Various Relationships toward John McCain - Pratiwi, Dita Ayu; Rukmini, Dwi; Sutopo, Djoko (Universitas Negeri Semarang, 2020)
An appraisal explains about language use on how the speakers or the writers negotiate their feeling with others or how the certain attitude is expressed in spoken or written text. The aim of this study is to identify the realization of appraisal in eulogies given by people of various relationships toward John McCain and explain the similarities and differences from those appraisals. The data are the clause of appraisals from the eulogy by George W. Bush, Meghan McCain, and Barack Obama. This study is discourse analysis and by attempting appraisal framework from Martin and White (2005) theory. The method of collecting data is documentation method. The result shows that all speakers used the appraising items of attitude, engagement and graduation. The former president George W. Bush produced 64 appraising items; her daughter Meghan produced 140 appraising items, while the former president Barack Obama produced 168 appraising items. The main similarity seems that George W. Bush and Meghan McCain are more dominant to use appraisal of attitude. Besides that, the difference show that Barack Obama is more dominant to use the feature of engagement. In the feature of attitude, all of them apply positive and negative items of un/happiness. In judgement and appreciation, the speakers do not apply the items of veracity and valuation. Besides that, all features of engagement used in their speech and dominant in the feature of disclaim. Meanwhile, the differences show that Barack Obama does not use the item of focus in appraisal of graduation. This study also gives the pedagogical implication for the language learners to use the appropriate expressions and to negotiate the feeling while doing the interaction or communication with others.